Numerical Analysis Of Ultra-Fine Package Assembly With SAC305-TiO2 Nano-Reinforced Lead Free Solder At Different Peak Temperature - Aziz, Asyraf Hasif (Universiti Sains Malaysia, 2018)
This thesis aims to determine the effect of peak temperature on the wetting region of ultra-fine lead-free solder joints reinforced with TiO2 nanoparticles in an electronic assembly and to investigate thermal strain on the intermetallic compound (IMC) layer. This study focuses on the nanoparticles distributions, fillet height and thermal strain of the IMC layer. Various weight percentages of the nanoparticles TiO2 with the SAC305 lead free reinforced solder and different peak temperature will be used. The main aim of this project is to obtain all the particles distributions, fillet height, thermal strain through the use of Ansys Workbench 18.2. The results obtained are validated by the experimental result obtained using high-resolution transmission electron microscope system equipped with an energy dispersive X-ray spectrometer (EDS), and a field emission scanning electron microscope coupled with an EDS and X-ray diffraction machine. The findings on this study shows that for higher temperature of the wetting region that ranges between 240°C and 255°C gives better particles distributions. Additionally, fillet height of the solder within this temperature range meet the requirement of the IPC standards that state that the measurement of the fillet formation for the joining of the device to the PCB pad should adhere to solder thickness of +25% of the termination height which is 0.0889mm. The best fillet height obtained is 0.1408988mm from using 250°C. The maximum thermal strain that exerted on the IMC layer recorded is from the sample of 255°C.